Resetting Priorities of Near-Zero Emission Energy Projects: Multi-Criteria Analysis - Hussam Fahmy; Rameen Abdelhady (International Journal of Sustainable Energy, 2023)
ABSTRACTEgypt’s national development plan aims to diversity energy resources and expand near-zero emission energy (NZEE) generation technologies. The target for NZEE’s share in the Egyptian energy basket is 20% by year 2030. There is a set of NZEE projects on the agenda of the decision-makers that needs reconsideration. This study goal is to assist decision-makers and stakeholders in reprioritising the implementation of these projects based on technical, economic, environmental, and social criteria. Multi-criteria analysis (MCA) was employed to rank five specific projects categorised under pumped storage hydropower, nuclear, clean coal, solar, and wind. The results showed that, for the non-biased set of weights, El Dabaa Nuclear Power Plant took the first rank. It has been also given the first priority according to environment activists’ biased weights. For the social biased weights, Benban Solar Park outranked all the other projects.